Pharmacological Transdifferentiation of Human Nasal Olfactory Stem Cells into Dopaminergic Neurons. (19th May 2019) - Chabrat, Audrey; Lacassagne, Emmanuelle; Billiras, Rodolphe; Landron, Sophie; Pontisso-Mahout, Amélie; Darville, Hélène; Dupront, Alain; Coge, Francis; Schenker, Esther; Piwnica, David; Nivet, Emmanuel; Féron, François; et al.
Abstract : The discovery of novel drugs for neurodegenerative diseases has been a real challenge over the last decades. The development of patient- and/or disease-specific in vitro models represents a powerful strategy for the development and validation of lead candidates in preclinical settings. The implementation of a reliable platform modeling dopaminergic neurons will be an asset in the study of dopamine-associated pathologies such as Parkinson's disease. Disease models based on cell reprogramming strategies, using either human-induced pluripotent stem cells or transcription factor-mediated transdifferentiation, are among the most investigated strategies. However, multipotent adult stem cells remain of high interest to devise direct conversion protocols and establish in vitro models that could bypass certain limitations associated with reprogramming strategies. Here, we report the development of a six-step chemically defined protocol that drives the transdifferentiation of human nasal olfactory stem cells into dopaminergic neurons. Morphological changes were progressively accompanied by modifications matching transcript and protein dopaminergic signatures such as LIM homeobox transcription factor 1 alpha (LMX1A), LMX1B, and tyrosine hydroxylase (TH) expression, within 42 days of differentiation. Phenotypic changes were confirmed by the production of dopamine from differentiated neurons. This new strategy paves the way to develop more disease-relevant models by establishing reprogramming-free patient-specific dopaminergic cell models for drug screening and/or target validation for neurodegenerative diseases.